2009
DOI: 10.1084/jem.20090889
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy is associated with bone marrow neuropathy and a depressed peripheral clock

Abstract: The present epidemic of diabetes is resulting in a worldwide increase in cardiovascular and microvascular complications including retinopathy. Current thinking has focused on local influences in the retina as being responsible for development of this diabetic complication. However, the contribution of circulating cells in maintenance, repair, and dysfunction of the vasculature is now becoming appreciated. Diabetic individuals have fewer endothelial progenitor cells (EPCs) in their circulation and these cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
210
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(231 citation statements)
references
References 23 publications
15
210
3
2
Order By: Relevance
“…The disautonomia associated to diabetes has been shown to affect also the BM, disrupt the peripheral clock and compromise the mobilization of endothelial and hematopoietic progenitors from the BM. 30,31 In addition, the BM neuropathy caused by chemotherapy has been shown to compromise hematopoietic recovery 4 ( Figure 1). Psychological and behavioral factors, including stress, depression and social isolation, are considered to contribute to the progression of certain types of cancer in humans.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%
“…The disautonomia associated to diabetes has been shown to affect also the BM, disrupt the peripheral clock and compromise the mobilization of endothelial and hematopoietic progenitors from the BM. 30,31 In addition, the BM neuropathy caused by chemotherapy has been shown to compromise hematopoietic recovery 4 ( Figure 1). Psychological and behavioral factors, including stress, depression and social isolation, are considered to contribute to the progression of certain types of cancer in humans.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%
“…(Am J Pathol 2016, 186: 1688e1700; http://dx.doi.org/10.1016/j.ajpath.2016.01.023) Microvascular complications of diabetes constitute a number of painful and debilitating conditions. Previously, we found that the bone marrow is susceptible to diabetic neuropathy, 1,2 which leads to denervation of stromal cells and altered secretion of growth factors and cytokines that ultimately shifts hematopoiesis toward a disproportionate increase of proinflammatory monocytes. 3,4 Consequently, monocytes are increased in the circulation and subsequently in tissues subject to diabetic complications, including retina, kidney, and brain.…”
mentioning
confidence: 99%
“…[82][83][84]136 The abnormal local response may also compromise the systemic input from the bone marrow or both local and systemic components could be blunted by co-existent disease. 34,71,121,137 In summary, it appears that the process that is DyR generates the stereotypical and even predictable wound response that is seen in AMD. As outlined in the previous sections of this study, all the necessary molecular ingredients appear to be present, to generate a normal reparative response.…”
Section: Bringing It All Together: Amd and Dyrmentioning
confidence: 99%